Sequential Weed Control Programs in No-Tillage Xtend Soybeans - D. E. Peterson; C. Thompson; C. L. Minihan (Kansas Agricultural Experiment Station Research Reports, 2017)
The development of glyphosate resistant weeds has greatly complicated weed control in soybeans. Roundup Ready 2 Xtend (dicamba tolerant) soybeans provide growers an alternative herbicide option for preplant and postemergence weed control in soybeans. Preplant programs that included dicamba provided excellent control of giant ragweed. Sequential programs consisting of Envive or Enlite plus glyphosate and dicamba preplant followed by postemergence treatments that included glyphosate and dicamba provided excellent control of henbit, giant ragweed, Palmer amaranth, and large crabgrass.
Keywords: Roundup Ready 2 Xtend soybeans; henbit; giant ragweed; Palmer amaranth; large crabgrass